Amazonomachy in the Mausoleum of Chersonesos Taurica: On the Historical and Mythological in Early-Hellenistic Art - Trofimova, Anna A. (Actual Problems of Theory and History of Art, 2023)
During the excavations in the southern suburb of Tauric Chersonesos, a mausoleum of a deified citizen of Chersonesos was discovered. This monument is unique for the Northern Black Sea region. The upper closed part of the building contained a sarcophagus with the remains of the hero. There was a temple-like structure on the top. A stone block with a relief depicting a scene of Amazonomachy was found on the territory of the heroon. The fragment belonged to the frieze located on the podium of naiskos. A close analogy to the iconography of that scene is presented on a sarcophagus found in Cyprus (now in the Vienna Kunsthistorisches Museum). The source of the iconography of battles between the Amazons and the Greeks, which became popular in the 4th century B.C., came from the friezes that decorated the architectural structures of the herons of Lycia and Caria. Under the influence of oriental samples, in the second half of the 4th century B.C., the subjects of the Amazonomachy appeared in the art of different regions in reliefs, mainly of funerary context. A striking example of such an influence in Attica can be considered the naiskos in Kallithea (now in the Archaeological Museum of Piraeus). Another parallel to the Chersonese discovery are the monuments found on Via Umbria in Tarentum. The Chersonese relief dates from 350 to 300 B.C., for which there are iconographic and stylistic grounds. When compared with the samples of the middle of the 4th century B.C., the iconography of the scene coincides in detail. The low relief features casually moving figures, and the ‘heroic diagonal’ is clearly read in the composition, which is the main artistic technique of Scopas used in the reliefs of the Mausoleum of Halicarnassus. The connection between the Amazonomachy and funeral naiskos can be traced throughout the second half of the 4th century B.C. The theme was used in the decoration of small funerary temples and sarcophagi in Southern Italy, Cyprus, and the Northern Black Sea region. The story of the battle with the Amazons, placed on the funeral structures in the cities of the ancient periphery, served as a universal way to give a heroic status to the representatives of the local elite. Although the images of Amazons were extremely popular on the Bosporus, the subjects of battles between the Greeks an Amazons were extremely rare in art of Chersonese. In the scene of the battle from the mausoleum, the details of the actual military ammunition of a warrior point to the real, not mythological character — the owner of the tomb. During this period the combination of the historical and the mythological can been found in many monuments, such as the Alexander Sarcophagus from Sidon, the sarcophagus from Soli, the Mausoleum at Halicarnassus, and the monument at Kallithea. Mythical personages and historical figures encounter each other in battles in the unified space of the funerary monument.